IMPLEMENTATION PROCESS OF STRATEGIC PLANNING AT DISTRICT GENERAL HOSPITAL - Fiany Dharyanti; Sutopo Patria Jati; Dodik Tugasworo Pramukarso (Universitas Airlangga, 2019)
Background: A strategic plan is the main reference for the management in carrying out activities to be better and more developed according to the customer’s needs. A preliminary study on documents was conducted at the District General Hospital of Dr. (H.C) Ir. Soekarno in Bangka Belitung Province which has implemented a strategic plan. It showed that there were gaps between expectation and implementation of strategic plan.Aim: This study aimed to analyze aspects affecting the strategic plan implementation, including communication, resources, disposition, and bureaucratic structure.Methods: This study was a descriptive study using a qualitative approach. Primary data were obtained through in-depth interview with 10 (ten) informants while secondary data were obtained from document analysis. The data processing and analysis were done using content analysis. The research was conducted from 2 to 31 January 2019 at the District General Hospital of Dr. (H.C) Ir. Soekarno.Results: The findings showed that the implementation process of strategic plans has some gaps. They include (1) ineffective communication, (2) resource factor (lack of quality and quantity of Human Resources, inadequate information, insufficient effectiveness of budget utilization), (3) weak disposition of some implementers, and (4) irrelevant and unadjusted bureaucratic structure.Conclusion: The implementation process of strategic plan has not worked appropriately because some aspects, such as communication, resources, disposition, and bureaucratic structure are not well-provided. This study suggests that formulators should represent all elements. The strategic planning has to be formulated by involving internal and external parties. Monitoring, evaluation, communication, and coordination among stakeholders have to be carried out. Resources need to be improved, and the hospital needs to develop organization structure and conduct disposition guide for executives and implementors.Keywords: implementation, strategic plan, hospital.